Length-weight relationship and condition factors of native freshwater fishes in the Hajar Mountain, Oman - Saud M. Al Jufaili; Aziza Saud Al Adhoobi; Humaid Darwish Al Mamari; Sara Yahya Al Hinai (Fisheries and Aquatic Sciences)
This study examined the length-weight relationship (LWR) and health status of five native freshwater fish species from seven wadis in the Hajar Mountain sampled once in March 2023. 1,896 fish specimens collected with foldable shrimp and crab fishing traps were analyzed for LWR parameters, growth types, and condition factors. The fish weight and length were measured using a digital electronic balance with precision of 0.01 g and a digital caliper, respectively. This analysis yielded coefficient of determination (R2) was ≥ 0.906, suggesting a good model fit. This study evaluated three well-being factors, Fulton’s condition factor (Kc), allometric condition factor (Ka), and relative condition factor (Kn). Generally, the LWR parameters exhibited variability between species and locations. The b-values ranged from 2.833 to 3.352 where the majority of species at all the sites revealed positive allometeric (b > 3) except for Garra shamal at Wadi Al Amirat, Aphaniops spp. at Wadi Al Khoud and Wadi Fanja, and Cyprinion muscatense at Wadi Surur, which displayed an isometric growth (b ≈ 3). Kc mean values ranged from 0.902 ± 0.085 to 1.889 ± 0.288 with the highest value observed in Aphaniops stoliczkanus at Wadi Al Amirat and the lowest value in C. muscatense at Ain Wadhah. The Ka average values show growth pattern in length-weight relationships where C. muscatense had the highest value of 2.124 ± 0.556 at Wadi Surur. The mean Kn values clustered around 1, which is common for healthy fish populations. There is a wide variation in growth patterns in LWRs and CFs among species and locations which might be attributed to the environment, food availability, reproductive status, and habitat characteristics. In this study, freshwater fish conservationists gained new information on CFs and updated LWR data. To improve the management of freshwater ecosystems we suggest conducting regular monitoring and creating protected areas at locations showing optimal fish conditions. Additionally, carrying out further studies that investigate the relationships between environmental parameters, fish CFs, gender, and seasonal variations to better inform conservation strategies.